Management of chronic migraine. (10th October 2022) - Hovaguimian, Alexandra; Roth, Julie
ABSTRACT: Chronic migraine is a neurologic disorder associated with considerable disability, lost productivity, and a profound economic burden worldwide. The past five years have seen a dramatic expansion in new treatments for this often challenging condition, among them calcitonin gene related peptide antagonists and neuromodulatory devices. This review outlines the epidemiology of and diagnostic criteria and risk factors for chronic migraine. It discusses evidence based drug and non-drug treatments, their advantages and disadvantages, and the principles of patient centered care for adults with chronic migraine, with attention to differential diagnosis and comorbidities, clinical reasoning, initiation and monitoring, cost, and availability. It discusses the international guidelines on drug treatment for chronic migraine and evaluates non-drug treatments including behavioral and complementary therapies and lifestyle modifications. Finally, it discusses the management of chronic migraine in special populations, including pediatrics, pregnancy, and older people, and considers future questions and emerging research in the field.